Bank concentration, competition and financial stability nexus in the East African Community: is there a trade-off? - Moses Nzuki Nyangu; Nyankomo Marwa; Ashenafi Beyene Fanta; Elinami J. Minja (Cogent Economics & Finance, 2022)
This paper examines bank concentration, competition, and financial stability nexus across five emerging countries (Kenya, Tanzania, Uganda, Rwanda and Burundi) within the East African Community (EAC). The methodological approach applied provides a critical and original contribution to the existing literature by testing the various theories explaining the relationships between bank concentration, competition, and stability. A two-step system Generalised Methods of Moments (GMM) is employed on a sample of 149 banks with 1,805 annual observations over the period 2001-2018. The findings reveal that high concentration and low competition lead to more financial stability and less probability of bank default risk. In addition, a non-linear relationship between competition and stability is not observed, revealing that greater competition undermines bank stability and makes banks more vulnerable to default risk. The findings thus lend to support the concentration-stability hypothesis that greater market power leads to more bank stability even after controlling for bank-specific, industry, and macroeconomic variables. The findings provide a significant policy contribution on the trade-off between bank concentration and competition, and the evaluation of financial stability.
Keywords: 330; Bank Concentration; Competition; Financial Stability; System GMM; East AfricanCommunity